Implementasi Kebijakan Bantuan Pangan Non Tunai Dalam Menanggulangi Kemiskinan di Kecamatan Kota Barat Kota Gorontalo - Pawawo, Aling S.; Tahir, Arifin; Sulila, Ismet (Media Hukum Indonesia (MHI), 2024)
This research aims to describe (1) the stages of implementing the Non-Cash Food Assistance policy in overcoming poverty in Kota Barat District, Gorontalo City (2) the determining factors for the success of implementing the Non-Cash Food Assistance policy in overcoming poverty in Kota Barat District, Gorontalo City, looking at communication aspects, sources power, disposition, and bureaucratic structure. The approach in this research uses a qualitative approach with descriptive research type. Data collection in research uses observation, interview and documentation techniques. The results of this research are (1) Stages of implementing the Non-Cash Food Assistance policy in overcoming poverty in Kota Barat District, Gorontalo City, which consists of stages, namely registration/preparation, socialization and education, distribution, and purchase of goods/utilization. These four stages have been carried out in accordance with existing policies. (2) The determining factors for the success of implementing the Non-Cash Food Assistance policy in overcoming poverty in Kota Barat District, Gorontalo City are seen from the aspects of communication, resources, disposition or attitude of implementers, as well as the bureaucratic structure which is quite good. However, there needs to be more communication in terms of socialization and education held by the West City sub-district and local sub-districts.